An Analysis Of Students’ Motivation In Teaching And Learning Process By Using Kahoot - Virga Putra Darma; Cecep Agus; Utami Rosalina (Al-Makki Publisher, 2022)
Kahoot! is a game-based learning platform used to review students’ knowledge, for formative assessment or as a break from traditional classroom activities. Play is a social-centred process, able to boost motivation and promote learning across all levels and ages. With the growing push for creativity in the classroom as well as the application of effective technology in teaching and learning. The key of teaching and learning process affects the students’ motivation as well as the learning goals. This study was carried out to describe an analysis of students’ motivation in learning process by using Kahoot! and to describe Kahoot! is effective to motivate students in learning writing process. This research used qualitative method with the observation and questionnaires as the instruments. It involved about three classes of the second grade students of SMPN 1 Sumber. The Sample was VIII A, VIII B, VIII H consist of 100 students. The data was analyzed descriptively. The findings showed that the result of ARCS (Attention, Relevance, Confidence, and Satisfaction) model of motivation defined the students motivated in learning process by using Kahoot! In addition, the result of the questionnaire Kahoot! was effetive to motivate student in learning writing process.